Productividad y nivel de vida de los agricultores del cultivo de arroz en el distrito de San Pedro de LLoc 2017-2018 - Loje Alva, Andres Lizardo (2019)
The present work of investigation has like objective relate the productivity of the culture of rice and as this influences in the level of life of the farmer. This report will help the farmer find information about the costs incurred in the planting process, classification, cereal varieties, and rice production in other regions of Peru and the main rice producers in the world. We must consider that the research carried out through a survey and interviews with Sampedran farmers, we find the discontent of the little help from their authorities when titling land, helping in machinery and places where they commercialize their production. Finally, we recommend the farmer to train and get more guidance through talks, seminars and implement new strategies on how to improve their production and marketing of cereal and how to invest the profits of their production in a business in order to obtain greater purchasing power that serve to improve the level of personal life, as a family.